Penggunaan Bahasa Indonesia sebagai Media Diplomasi antara Indonesia dengan Thailand melalui Program Pengajaran Bahasa Indonesia untuk Penutur Asing (BIPA) pada Tahun 2011-2015 - Anggara Darma, Anak Agung Ngurah; Fasisaka, Idin; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT The development of world situation, actors, and technology these days has made traditional diplomacy shifts to become more modern . On it’s development, diplomacy is not only limited to be explained as traditional diplomacy that is only related to politics and military, but also with modern diplomacy it diversified into the field of diplomacy where it becomes more widespread. This is also means that there would be more instrument that diplomacy can use for it’s track, one of the instrument is using of cultural instruments. The Government of Indonesia through BIPA hopes it can introduce and consolidate the Indonesian language to ASEAN level through Thailand as the target country. This study aims to providing an explanation of how the Indonesian government uses the Indonesian language as an instrument of a nation branding concept to provide a positive image to the Indonesian nation, from this study it will also describe a descriptive analysis of Indonesian Language strengths that can be used as an instrument to strengthen the soft power of a country through the concept of cultural diplomacy .   Keywords :Indonesian Language, BIPA, Nation Branding, Cultural Diplomacy